Acute doxorubicin-induced cardiotoxicity is associated with matrix metalloproteinase-2 alterations in rats - Polegato, Bertha Furlan [UNESP] (2015)
Background: Doxorubicin can cause cardiotoxicity. Matrix metalloproteinases (MMP) are responsible for degrading extracellular matrix components which play a role in ventricular dilation. Increased MMP activity occurs after chronic doxorubicin treatment. In this study we evaluated in vivo and in vitro cardiac function in rats with acute doxorubicin treatment, and examined myocardial MMP and inflammatory activation, and gene expression of proteins involved in myocyte calcium transients. Methods: Wistar rats were injected with doxorubicin (Doxo, 20 mg/kg) or saline (Control). Echocardiogram was performed 48 h after treatment. Myocardial function was assessed in vitro in Langendorff preparation. Results: In left ventricle, doxorubicin impaired fractional shortening (Control 0.59 +/- 0.07; Doxo 0.51 +/- 0.05; p < 0.001), and increased isovolumetric relaxation time (Control 20.3 +/- 4.3; Doxo 24.7 +/- 4.2 ms; p = 0.007) and myocardial passive stiffness. MMP-2 activity, evaluated by zymography, was increased in Doxo (Control 141338 +/- 8924; Doxo 188874 +/- 7652 arbitrary units; p < 0.001). There were no changes in TNF-alpha, INF-gamma, IL-10, and ICAM-1 myocardial levels. Expression of phospholamban, Serca-2a, and ryanodine receptor did not differ between groups. Conclusion: Acute doxorubicin administration induces in vivo left ventricular dysfunction and in vitro increased myocardial passive stiffness in rats. Cardiac dysfunction is related to myocardial MMP-2 activation. Increased inflammatory stimulation or changed expression of the proteins involved in intracellular calcium transients is not involved in acute cardiac dysfunction.